Daisy and the egg - Simmons, Jane. (Boston : Little, Brown, 1998)
Daisy the duckling eagerly awaits the arrival of a new brother or sister, even helping Mama Duck sit on the egg while they wait for it to hatch.
"First published in Great Britain in 1998 by Orchard Books"--T.p. verso.
Companion to: Come along, Daisy!
Booklist.
Kirkus Starred.
New York Times.
2.8.
Keywords: Animals -- Infancy -- Fiction; Brothers and sisters -- Fiction; Ducks -- Infancy -- Fiction; Eggs -- Fiction; Animal babies; Ducks -- Fiction; Eggs -- Fiction; Siblings -- Fiction